Model Akuntabilitas Organisasi Non Profit pada Masjid - Eka Siskawati; Ferdawati; Firman Surya (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2015)
The purpose of this study is to examine accountability model for mosque and its relation to organisational culture and organisational learning. Data were collected from 60 mosques located in Padang through distributed questionaire to mosques’ managers. Findings reveal that only internal accountability positively significant affects organisational culture and organisational learning. While upward accountability significantly does not affect organisational culture which implies that lower intention of donor to monitoring how do mosques’ management spend the donation. This lower control from donor may attributed to the spiritual aspect of donor who believe that anything good that donated to mosque will be rewarded by Allah SWT, regardless the way management to allocate it. Other explanation is that it may attribute to the difficulty in classifying between donator and beneficiary, because in mosque organisation a donator is also a beneficiary of mosque services and vice versa. Downward accountability does not affect organisational culture, this implies that there is a weak responsibility of mosques’ managers ini Padang that serve beneficiary. Regarding to the low degree of accountability to beneficiary (congregation), it contradicts to the main purpose of mosque’s establishment. Abstrak ), it contradicts to the main purpose of mosque’s establishment. Tanggal revisi 04-02-2015 Tanggal diterima 06-02-2015 Keywords: Mosque Accountability Organisational Culture Organizatinal Learning Kata kunci: Abstrak Masjid Akuntabilitas Budaya Organisasi Pembelajaran Organisasi Penelitian ini bertujuan untuk menguji model akuntabilitas masjid dan hubungannya dengan budaya organisasi dan pembelajaran organisasi. Data penelitian ini dikumpulkan terhadap 60 masjid yang berlokasi di kota Padang. Hasil penelitian ini menemukan bahwa akuntabilitas „keatas‟ tidak berpengaruh signifikan terhadap budaya organisasi, yang mengimplikasikan bahwa lemahnya tuntutan donatur terhadap akuntabilitas pengelolaan dana oleh manajemen masjid. Hal ini mungkin disebabkan oleh keyakinan spiritual yang dimiliki oleh donatur, bahwa apapun yang diniatkan oleh donatur untuk kemakmuran masjid akan mendapat pahala dari Allah SWT terlepas dari bagaimana pengurus masjid mengelolanya. Penjelasan lainnya adalah karena kaburnya batas dan sekat dalam mengelompokkan antara donatur, pengurus, dan jamaah, karena dalam suatu masjid seorang donatur pada saat yang sama juga merupakan seorang jamaah dan begitu juga sebaliknya. Akuntabilitas „kebawah‟ juga menunjukkan hasil yang tidak signifikan berpengaruh terhadap budaya organisasi, hal ini mengimplikasikan rendahnya sikap akuntabilitas pengurus masjid terhadap jamaah. Hanya akuntabilitas „ke dalam‟ berpengaruh signifikan terhadap budaya organisasi, yang mengindikasikan tingginya rasa tanggungjawab pengurus masjid terhadap sesama staf dalam menjaga visi dan misi masjid.